Microbial Uricase and its Unique Potential Applications - Elbanna Khaled; Alshareef Atheer; Neyaz Leena A.; El-Readi Mahmoud Z.; Abulreesh Hussein H. (Postępy Mikrobiologii, 2024)
The uricase enzyme yields allantoin, hydrogen peroxide, and carbon dioxide by catalyzing the oxidative opening of the purine ring in the urate pathway. This enzyme is important for biochemical diagnosis and reduces toxic urate accumulation during various diseases (hyperuricemia, gout, and bedwetting). Direct urate oxidase injection is recommended in renal complications-associated gout and to prevent chemotherapy-linked hyperuricemia disorders. Thus, uricase is a promising enzyme with diverse applications in medicine. Microbial production of uricase is featured by high growth rates, cost-effective bioprocessing, and easy optimization of the medium. Microbes produce the enzyme extracellular or intracellular. Extracellular uricase is preferred for biotechnological applications as it minimizes time, effort, and purification processes. This review provides insights into uricase-producing microbes, bacterial uric acid degradation pathways, degrading enzymes, and uricase-encoding genes.